Demographic Aspects of Human Capital Development in Russia and Its Regions - Iontsev, Vladimir Alekseyevich; Magomedova, Aminat Gimbatovna (Economy of Regions, 2015)
In the article, the current demographic situation that has developed in Russia and can be described as a demographic crisis is analysed. One of its most important characteristics is the negative qualitative changes that occur in the population. Modern information technology contributes a lot to this process. The negative qualitative changes in the population, which have begun in the second half of the 1980s and have increased in present-day Russia, prevent the development of human capital in the country. In addition to that, the authors give their own interpretation of the concept of "human capital". The purpose of the paper is to justify the primacy of the demographic factor in the formation and development of human capital. Migration in the form of a brain drain also has a negative impact on the development of human capital in Russia and its regions. The human development index calculated for the country as a whole and for its regions confirms the above-mentioned. In the paper, the methods of demographic analysis, the demographic indicators and indexes, which can serve to analyse the qualitative characteristics of the population, are utilized. The authors arrive at the conclusion that at the present stage, it is impossible to develop human capital without solving the demographic problems. This is especially true for some regions of Russia. Awareness of this will contribute to the more efficient management of demographic processes, which, in turn, will guarantee the positive development of human capital, strengthening and development of the Russian economy and society as a whole.